'Ontological Planning' As a New Approach in Urban Development - Ahmet Alkan; Havva Alkan Bala (European Regional Science Association (ERSA), 2014)
"Ontological Planning" as a new concept, this paper will attempt to clarify an interpretation of the existential philosophy in urban dimension, the adaptability of this interpretation to physical planning and the main principles of ontological planning. These principles will be explained via applications performed at the Mevlana Museum, which is an important site on a global scale, and its surroundings. New concepts have been developed in the planning process in parallel to the processes of urbanization, growth, industrialization and urban development. The social, economic and spatial planning efforts in these concepts and methods aimed to generate solutions that have been inclusive of problems and sustainable. However, something has remained missing during the planning of the city, which is complex and big and constantly creates problems. Planning has usually proven inadequate in searches for solutions to urban problems. The inadequacy of existing concepts and approaches has become more and more apparent in areas of cities that are of importance in terms of historical and architectural heritage. This new approach, which is based on longitudinal observations and the assumption that a relationship can be established between the space and the existentialist philosophy, has been opened to debate in the scientific world. The ontological planning approach, which is presented in this paper, is not a new method, nor is it a hypothesis that excludes the existing methods. On the contrary, it is an attempt to add a new and long-awaited point of view by integrating the "existential philosophy" into the integrative (holistic) and sustainable planning process. Ontological planning will take steps that will enable a fusion of the society and the space via; ? Space planning defined by the idea of existence (being), ? Addition of moral (ethical and aesthetic) criteria to technique, ? Establishment of the relationship between space and love ? Adding spirit to the space ? Addition of the morphological energy of the space to planning.
Keywords: 330; Urban Planning; Ontological Planning; Mevlana Celaleddin Rumi; Konya